The time course of short-term hypertrophy in the absence of eccentric muscle damage - Stock, Matt S.; Mota, Jacob A.; DeFranco, Ryan N.; Grue, Katherine A.; Jacobo, A. Unique; Chung, Eunhee; Moon, Jordan R.; DeFreitas, Jason M.; Beck, Travis W. (European journal of applied physiology, 2017)
Background It has been proposed that the increase in skeletal muscle mass observed during the initial weeks of initiating a resistance training program is concomitant with eccentric muscle damage and edema. Purpose We examined the time course of muscle hypertrophy during 4 weeks of concentric-only resistance training. Methods Thirteen untrained men performed unilateral concentric-only dumbbell curls and shoulder presses twice per week for 4 weeks. Sets of 8–12 repetitions were performed to failure, and training loads were increased during each session. Subjects consumed 500 ml of whole milk during training. Assessments of soreness, lean mass, echo intensity, muscle thickness, relaxed and flexed arm circumference, and isokinetic strength were performed every 72 or 96 h. Results Soreness, echo intensity, relaxed circumference, and peak torque data did not significantly change. Significant increases in lean mass, muscle thickness, and flexed circumference were observed within seven training sessions. Lean mass was elevated at tests #7 (+109.3 g, p = .002) and #8 (+116.1 g, p = .035), with eight different subjects showing changes above the minimal difference of 139.1 g. Muscle thickness was elevated at tests #6 (+0.23 cm, p = .004), #7 (+0.31 cm, p < .001), and #8 (+0.27 cm, p < .001), with ten subjects exceeding the minimal difference of 0.24 cm. There were no changes for the control arm. Conclusion In individuals beginning a resistance training program, small but detectable increases in hypertrophy may occur in the absence of eccentric muscle damage within seven training sessions.